'I Will Lead You to the River': Women, Water, and Warfare in the Roman de Thèbes, Roman de Troie, and Early Chronicles of the First Crusade. Issue 2 (26th September 2018) - Harwood, Sophie
This article analyses the connection between women, water, and warfare in early chronicles of the First Crusade and two contemporaneous romances from the Old French Troy tradition. It considers the way women are shown providing water to men, using water for washing and cleaning services, and how they inhabit watery spaces. It contrasts the way in which women are overwhelmingly associated with water, while men seem to be associated with land and foodstuffs. It explores the idea that watery spaces are essentially feminised and duties that involve water are almost exclusively the domain of women. Could this feminisation have occurred because water, as well as being essential, could also be dangerous and threatening, mirroring a misogynistic trope that women were also dangerous and threatening? Perhaps the gendering of water in these 12th-century texts can be seen as participating in the larger debate over gender and women that was going on throughout the Middle Ages.